Importance of one- and two-photon transitions in the strong-field dissociation of NO2+ - Jochim, Bethany; Zohrabi, M.; Gaire, B.; Uhlíková, Tereza; Carnes, K. D.; Wells, E.; Esry, B. D.; Ben-Itzhak, I. (My University, 2021)
Employing a coincidence three-dimensional momentum imaging technique, we investigate the ultrafast, intense laser-induced dissociation of a metastable NO2+ ion beam into N++O+. Based on the kinetic energy release and angular distributions, measured using both 774-nm and second-order-harmonic 387-nm pulses, we show that the main processes driving dissociation in pulses of about 1014W/cm2 peak intensity are one- and two-photon transitions from the X2Σ+ ground state to the A2Π first-excited state. First-order perturbation theory calculations also corroborate these findings.